PENGGUNAAN MEDIA SOSIAL TERHADAP KEJADIAN DEPRESI, KECEMASAN DAN STRES PADA MAHASISWA: USE OF SOCIAL MEDIA ON EVENTS OF DEPRESSION, ANXIETY AND STRESS AMONG UNIVERSITY STUDENTS - Budury, Syiddatul; Fitriasari, Andikawati; -, Khamida (Bali Medika Jurnal, 2019)
The use of Social media with high intensity is happening in adolescence. They are interacting each other by social media. This triggers health problems, not only physical but also mental health. The aims of this research was to analyze the effect of the use of social media on depression, anxiety and stress among university students. the research design was cross sectional study, and the sample was 80 students taken by simple random sampling. independent variable was social media usage and dependent variable were depression, anxiety and stress. The data was taken using social media addiction scale, and depression, anxiety, stress scale (DASS 21). it was analyzed by using Manova statistic test. the result showed that 65 students (81.5) was medium user, 9 students (11.5%) light user and 6 students (7.5%) as heavy user. the Manova test showed that P Value at Depression was 0.03, Anxiety got 0.04 and the p Value for stress was 0.02. it means that there was effect of social media use to depression, anxiety and stress.